Analysis of the Effect of NPF, CAR, and FDR on the Profitability of Sharia Commercial Banks in Indonesia for the Period 2017-2022 - Lina Nugraha Rani; Fahrul Rozi (Institut Agama Islam YPBWI Surabaya, 2026)
This study examines the impact of Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR), and Financing to Deposit Ratio (FDR) on the profitability of Islamic Commercial Banks in Indonesia during the 2017–2022 period. Using a quantitative approach, this research employs panel data regression analysis based on secondary data obtained from the financial statements of nine selected banks through purposive sampling. Profitability is proxied by Return on Assets (ROA), while NPF, CAR, and FDR serve as key financial indicators representing credit risk, capital adequacy, and liquidity, respectively. The findings reveal that partially, NPF and FDR have a significant negative effect on profitability, indicating that higher financing risk and suboptimal fund distribution reduce bank performance. Meanwhile, CAR shows a positive but statistically insignificant relationship with profitability, suggesting that capital adequacy alone does not directly drive profit generation. Simultaneously, all independent variables significantly influence profitability. These results highlight the importance of effective risk management, particularly in controlling non-performing financing and optimizing liquidity, to enhance the financial performance and stability of Islamic banking institutions.